GAMBARAN POLA KONSUMSI JUNK FOOD DAN SOFT DRINK RESIKO PENYAKIT TIDAK MENULAR HIPERTENSI REMAJA DI SMA SANTO PETRUS MEDAN TAHUN 2024 - Magda Siringo-ringo; Indra Hizkia P; Rusliana (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Background: Hypertension is the factor that results in the greatest mortality on earth at a young age. In Indonesia, the most common cause of death is hypertension, which is included in the category of non-communicable diseases (NCDs). Consuming too much junk food results in hypertension. Consuming soft drinks excessively will increase the number of calories that the body stores as fat. The accumulation of fat in the body can lead to blockage of blood flow and the formation of plaque or atherosclerosis, potentially leading to hypertension. Objective: This study aims to identify the pattern of junk food and soft drink consumption patterns at the risk of non-communicable diseases of hypertension. Methods: The researcher used a quantitative method, the populations are 210 people, with a sample of 68 people, using a simple random sampling technique, data collection using a food frequency questionnaire (FFQ) and measuring the blood pressure of students. Results: The study found that the consumption pattern of junk food in the frequent category is 60.3%, the frequency consumption pattern of junk food in the category is 55.9%, the category is less than 26.5%, the category is more than 17.6%, the consumption pattern of the amount of junk food in the category is 51.5%, the category is less than 36.7%, the category is over 11.8%, The consumption pattern of soft drinks in the frequent category is 41.2%, the frequency consumption pattern of soft drinks in the fair category is 51.5%, the less than 35.3%, the more than 13.2%, the consumption pattern of the amount of soft drinks in the moderate category is 48.5%, the less than 42.6%, the more than 8.8%, Adolescents who have a history of normal hypertension (32.4%). Advice: Adolescents are expected to reduce the habit of consuming junk food and soft drinks too often, because these types of foods and drinks can increase the risk of various dangerous diseases such as hypertension.